Faktor-Faktor Mempengaruhi Kritikan Riwayat Sirah: Satu Kajian Terhadap Nūr Al-Dīn Al- Ḥalabī Dalam Karyanya Al-Sīrah Al- Ḥalabiyyah - Ahmad Salahuddin M Azizan; Zulhilmi Mohamed Nor; Muhammad Akmalludin Mohd Hamdan (Fakulti Pengajian Quran dan Sunnah, 2024)
8TH International Prophetic Conference SWAN 2022 5th to 6th October 2022 (Hybrid Conference) Organized by: Faculty Of Quranic And Sunnah Studies